Success in bone marrow failure? Novel therapeutic directions based on the immune environment of myelodysplastic syndromes. Issue 2 (8th June 2017) - Cull, Alyssa H; Rauh, Michael J
Abstract : Review on how marrow cells contribute to the abnormal MDS microenvironment, and how they may be targeted through novel therapeutics. Abstract: Myelodysplastic syndromes (MDS) are clonal neoplasms of aging that are associated with BM failure, related cytopenias, fatigue, susceptibility to infections, bruising, bleeding, a shortened lifespan, and a propensity for leukemic transformation. Most frail, elderly patients are not candidates for curative allogeneic BM transplantations and instead receive expectant management, supportive blood transfusions, or empirical, nontargeted therapy. It has been known for some time that MDS arises in an abnormal BM immune environment; however, connections have only recently been established with recurring MDS-associated mutations. Understanding how mutant clones alter and thrive in the immune environment of marrow failure at the expense of normal hematopoiesis opens the door to novel therapeutic strategies that are aimed at restoring immune and hematopoietic balance. Several examples are highlighted in this review. Haploinsufficiency of microRNAs 145 and 146a in MDS with chromosome 5q deletions leads to derepression of TLR4 signaling, dysplasia, and suppression of normal hematopoiesis. Moreover, mutations of TET2 or DNMT3A —regulators of cytosine methylation—are among the earliest in myeloid cancers and are even found in healthy adults with cryptic clonal hematopoiesis. In innate immune cells, TET2 and DNMT3A mutations impair the resolution of inflammation and production of type I IFNs, respectively. Finally, a common result of MDS-associated mutations is the inappropriate activation of the NLRP3 inflammasome, with resultant pyroptotic cell death, which favors mutant clone expansion. In summary, MDS-associated mutations alter the BM immune environment, which provides a milieu that is conducive to clonal expansion and leukemic progression. Restoring this balance may offer new therapeutic avenues for patients with MDS.